THE USE OF MIND MAP TECHNIQUE IN TEACHING READING FOR 9th GRADE OF JUNIOR HIGH SCHOOL STUDENTS - Simanjuntak, Gracella Andaresta; Simanjuntak, Meiyanti; Sihombing, Anggita (REVIEW OF MULTIDISCIPLINARY EDUCATION, CULTURE AND PEDAGOGY, 2022)
The purpose of this research is to find out a technique that can be used as a technique for the teacher to teach reading skill to the students. In this case, the researchers investigate mind map technique to be used in teaching reading skill. The researchers chose classroom action research in collecting the data. Therefore, there are two cycles that the researchers have been held in the teaching and learning process. From the results of the research, researchers found improvement of the students’ scores in reading text. It means that mind map technique is one technique that has good influence and has benefit for the students so that they be able to read better text in English. The subject of this research was the 9th grade students of class XI-4 in SMP N 2 Siantar, which is contain of 32 students.